Identity, Subjectivity and Symptom in Contemporaneous Era - Yvana Coutinho de Oliveira (Universidade de Fortaleza, 2003)
This article discusses the trio identity, subjectivity and symptom in modern times reflectingabout the individual's working through and subjectivity processes. This is a bibliography study of psychodynamic orientation. The author emphasizes the importance of rethinking and understanding the ways in which individuals process their own subjectivity. Various modern time symptoms result from the fact that individuals end up crushed by their own singularities.